2018
DOI: 10.4269/ajtmh.17-0752
|View full text |Cite
|
Sign up to set email alerts
|

Hepatitis B Infection among Parturient Women in Peri-Urban Ghana

Abstract: Global evidence suggests that hepatitis B viral (HBV) infection is endemic in Africa and perinatal transmission remains one of the most important modes of HBV transmission in this area. This cross-sectional survey examined the seroprevalence and knowledge of hepatitis B among pregnant women attending antenatal clinic (ANC) in a mission hospital in Ghana. Systematic sampling technique was used to recruit 196 pregnant women. The level of statistical significance was set at 0.05 alpha level. The hepatitis B preva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

5
4

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 23 publications
1
18
0
Order By: Relevance
“…It is estimated that 1 in every 10 persons in South Sudan is infected with either HBV or hepatitis C virus (28). Our findings also support recent observations in SSA, where the burden of HBV in pregnant sub-populations remains proportionately high in localities with a high HBV population-level endemicity (29)(30)(31)(32)(33).…”
Section: Discussionsupporting
confidence: 91%
“…It is estimated that 1 in every 10 persons in South Sudan is infected with either HBV or hepatitis C virus (28). Our findings also support recent observations in SSA, where the burden of HBV in pregnant sub-populations remains proportionately high in localities with a high HBV population-level endemicity (29)(30)(31)(32)(33).…”
Section: Discussionsupporting
confidence: 91%
“…In the Eastern region, 10.6% prevalence was reported among 1500 pregnant women [6]. It was also lower than other prevalence rates reported in Ghana [15,23,24].…”
Section: Discussionmentioning
confidence: 90%
“…The researchers also reported that 90.5% had heard of HBV but lacked knowledge of transmission routes and prevention methods [23]. A similar study among pregnant women attending antenatal care in a mission hospital in Ghana reported 10.2% HBV prevalence, high awareness, and poor accurate knowledge about HBV [24]. However, no study on HBV knowledge, vaccination status, perceptions, or attitudes was found to have been conducted in the Northern region and more so in the Nanumba North and Nanumba South districts of the region.…”
Section: Plos Onementioning
confidence: 97%
“…In fact, in Ghana, hepatitis B is often misconstrued to be more dangerous than HIV [11], and, in light of the already extensive stigmatisation of PLHIV, it is likely that the associations made between hepatitis B and HIV strengthened our participants' commitment not to disclose their chronic hepatitis B status. The perception that hepatitis B is more dangerous than HIV is driven by a lack of knowledge, often resulting from the provision of inaccurate hepatitis B information by herbal practitioners on various media platforms in Ghana [38]. One common message used by herbal practitioners to attract customers to purchase their products is that hepatitis B is more dangerous than HIV.…”
Section: Discussionmentioning
confidence: 99%